Detection of chlamydiae from the upper respiratory tract of healthy and diseased draught equines - PRIYANKA, PRIYANKA; CHAHOTA, R; GUPTA, S; BHARDWAJ, B; SHARMA, M (The Indian Journal of Animal Sciences, 2019)
The present investigation was conducted to study the prevalence and molecular characterization of chlamydiae associated with the respiratory infections of equines in the Sub-Himalayan region of India. Equine nasal swab samples (119) from 20 diseased and 99 apparently healthy equines were collected and tested by family Chlamydiaceae specific nested PCR based on ompA gene, besides 89 serum samples for AGPT. The molecular characterization of chlamydial species/strains was done by analyzing variation in VD II region of ompA gene. The chlamydia infections were detected in 48.74% of the nasal swabs (55% in diseased and 47.47% in apparently healthy animals) by nested PCR. Prevalence of two genetically variant strains of Chlamydia abortus and a single strain of Chlamydia psittaci was detected. AGPT showed 4.49% seropositive equines. High prevalence of chlamydiae was found among equines in the Sub-Himalayan region of India in Himachal Pradesh in both healthy and diseased equines.